The Spatial Concentration of Manufacturing Industry Workforce: Is There a Change? - Erni Febrina Harahap (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
The purpose of this paper is to describe the spatial concentration of manufacturing industry and examines the factors that influence it. The method of analysis using entropy theil index and pooling of data with the object of manufacturing industry employment as a means of measuring the concentration of spatial and time series data during the study period, namely from 2008 to 2016 and the cross section with 9 industry sectors according to the two-digit industrial classification ISIC Revision 3 in 30 provinces of Indonesia. The data was collected using secondary data from the Central Statistics Agency (BPS), Data and Information Center (Pusdatin), and the Agency for Industrial Research and Development (BPPI) Ministry of Industry and related literature. Spatial gaps between islands manufacturing industry clearly visible where the Theil entropy index value in Java is very high which means the manufacturing industry is concentrated on the island, while on other islands are very low. While the calculation of theil index for spatial gaps in the island shows that the island of Sumatra occurred in a larger gap than the other islands. This happens due to the island of Sumatra, manufacturing industry workers accumulate only in some provinces, that is most dominant in the provinces of North Sumatra and South Sumatra and Lampung. While the level of the lowest spatial concentration is the islands of Bali and Nusa Tenggara, which means the manufacturing industry employment relative spread (dispersion). Regression results show that the model of spatial concentration was significantly affected by variables that are used, except for human capital variables. And this model is rejected in part the hypothesis of neoclassical theory (NCT), but supports the new trade theory (NTT) and the new economic geography (NEG). Keywords: Theil Entropy index, pooling data, spatial concentration, neoclassical theory, new trade theory